An uncommon severe clinical course of European tick-borne encephalitis. - Herzig, Roman; Patt, Carl Matthias; Prokes, Tamara (Biomedical papers, 2002)
Tick-borne encephalitis (TBE) is the major European arbovirosis. Man is often infected by the tick bite; laboratory infections as well as infections after consumption of nonpasteurized milk have occasionally been reported. TBE typically takes a biphasic course. After an incubation period (7-14 days usually), the prodromal symptoms occur. The first stage of the disease lasts 1-8 days. After an afebrile asymptomatic interval of approximately 1-week the second stage develops, in which TBE may manifest as isolated meningitis, meningoencephalitis, meningoencephalomyelitis and/or radiculitis. The mortality rate is 0-3.3%. There is high frequency of sequelae. Patients who have suffered from a TBE infection are immune for the rest of their lives. At present there is no effective antiviral therapy and management is strictly supportive. Active immunization against TBE is recommended for all subjects living in and travelling to areas of risk. Passive immunization is recommended only within 48 hours after a tick bite. The authors present the case report of 75-years old female subject, who suffered from the uncommon severe clinical course of TBE--with the development of consciousness impairment, tetraplegia, and dyspnoea (demanding ventilatory support). Her state was complicated by the transient left side faciobrachial motor Jackson's convulsions, blood pressure instability, heart arrhythmia, respiratory infection, anemia, and by the development of critical illness neuropathy. Although she made slow progress during treatment, she died on the 114th day because of suspected aspiration.
Keywords: Tick-borne encephalitis / Meningoencephalomyelitis / Clinical course / Mortality